Cultural Barriers and Challenges of Ma’had Aly: The Path towards a Competitive Islamic Higher Education Institution - Munifah Munifah; Intan N.N. Puspitasari; Hilmi Husaini Zuhri; Achmad Yani; Asyifa Nadia Jasmine; Agustina Kurniasari (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The dominance of the local realm and traditional values in Ma’had Aly has been deemed irrelevant in light of the recent need for modern education. Despite its significant potential, Ma’had Aly faces critical cultural challenges that hinder its transformation into a competitive and sustainable Islamic higher education institution. Accordingly, this article examines the cultural factors that influence governance, curriculum development, and technological integration within the context of ma’had aly, a pesantren-based model of Islamic higher education. Utilizing a qualitative case study approach, this research gathered data from interviews with participants, documents, and observations. It was also supported by web scraping techniques—drawing from news outlets, websites, and social media platforms relevant to ma’had aly discourse. The findings revealed that Ma'had Aly faced cultural barriers in several key aspects. First, the dominance of conservatism is signified by the educational orientation that relies on classical texts, Islamic teachings, organisational structure, and institutional management that is not based on modernisation-administrative principles. Secondly, there is a traditional management approach that tends to be less adaptive, characterised by a centralised organisation, an alum majority in the staff structure, centralised policy, and central decision-making. Finally, this research identified curriculum decontextualization in the areas of curriculum composition, orientation, and implementation, which is considerably inflexible in the context of globalization and technological enhancement. Thus, this research highlights the need for visionary leadership that is responsive to change and for comprehensive institutional reform.